Consumption of “Diabetes Risk Reduction Diet” and Odds of Breast Cancer Among Women in a Middle Eastern Country - Ebrahimi Mousavi, Sara; Bagheri, Amir; Benisi-Kohansal, Sanaz; Azadbakht, Leila; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2022)
Background: Given the role of insulin resistance in several cancers, we hypothesized that consumption of a diet that reduces insulin resistance might lower the risk of breast cancer. Objective: The present study was designed to assess the association between consumption of “diabetes risk reduction diet” (DRRD) and odds of breast cancer among a large group of women in a Middle Eastern country. Methods: This population-based case-control study enrolled 350 newly diagnosed cases of stage I-IV breast cancer and 700 age-matched apparently healthy individuals as controls. We collected dietary data via a validated 106-item Willett-format semi-quantitative dish-based food frequency questionnaire. A DRRD score was included based on 9 dietary factors (cereal fiber, coffee, nuts, whole fruits, ratio of polyunsaturated to saturated, trans fat, sugar-sweetened beverages, red and processed meat, lower glycemic index). For food and nutrient items with a protective association with diabetes in earlier studies, participants were given the score as the quintile of that food item, but for food groups with unfavorable association with diabetes, we did vice versa. Total DRRD score ranged from 5 to 45. Results: Mean age of cases and controls was 65.28 and 61.04 y. Mean BMI of patients with breast cancer and controls was 25.5 and 21.0. We found that individuals with the greatest adherence to the DRRD were 0.41 times less likely to have breast cancer than those with the lowest adherence (OR: 0.59; 95% CI: 0.38, 0.90, P-trend=0.002). Stratified analysis by menopausal status indicated a significant inverse relationship in postmenopausal women (OR: 0.57; 95% CI: 0.36–0.90), but not in premenopausal women (OR: 0.76; 95% CI: 0.19–2.96). Moreover, by BMI status, we found statistically significant inverse association between adherence to the DRRD and odds of breast cancer among normal-weight women (OR: 0.59; 95% CI: 0.36, 0.98) but not in overweight women (OR: 0.66; 95% CI: 0.31, 1.40) Conclusions: Significant inverse associations were found between adherence to DRRD and breast cancer, especially among postmenopausal and normal-weight women.